Strategi Pembelajaran Tahfidzul Qur’an di Madrasah Ibtidaiyah Dipanegara Ranterejo - Fauziyah, Zuhrotul; Irodati, Fibriyan (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The aims of this research are: (1) to find out the strategy for learning Tahfidzul Qur'an at Madrasah Ibtidaiyah Dipanegara Ranterejo (2) to find out the supporting and inhibiting factors in the process of learning Tahfidzul Qur'an at Madrasah Ibtidaiyah Dipanegara Ranterejo. This research uses qualitative research methods, namely researchers make observations in the field to find out phenomena or facts. The subjects in this research were the madrasa head, Tahfidzul Qur'an teacher, and students of the Tahfidzul Qur'an class at Madrasah Ibtidaiyah Dipanegara Ranterejo. Data collection techniques are interviews, observation and documentation. The data analysis used is data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that: (1) The Tahfidzul Qur'an learning strategy at Madrasah Ibtidaiyah Dipanegara Ranterejo includes: a large classical strategy which includes supporting material such as tajwid science material, memorizing daily prayers, prayers, stories or tales Islamic and joint tadarus activities, individual strategies which include istimror activities or connecting verses, muraja'ah or rote repetition and new memorization deposits, and small classical strategies which include reading sima'. (2) Supporting factors in learning Tahfidzul Qur'an at Madrasah Ibtidaiyah Dipanegara Ranterejo include: motivation, intelligence, ideal age, and student environment. Meanwhile, inhibiting factors in Tahfidzul Qur'an at Madrasah Ibtidaiyah Dipanegara Ranterejo include: the emergence of a feeling of laziness to memorize, lack of time management, fatigue which results in drowsiness, lack of concentration, still liking to play with friends when learning takes place and health which is often disturbed.